SrCo0.85Fe0.15O2.62 – Oxygen Deficient "314‐type" Perovskite; a Highly Efficient Cathode for Solid Oxide Fuel Cells. Issue 3 (9th June 2017) - Marik, S.; Nicollet, C.; Channabasappa, M.; Fourcade, S.; Wattiaux, A.; Duttine, M.; Decourt, R.; Bassat, J.‐M.; Toulemonde, O.
Abstract: Structure, electrical conductivity and electrochemical performance for a new oxygen deficient perovskite material with composition SrCo0.85 Fe0.15 O2.62 is explored here. It crystallizes in a "314‐type" oxygen‐vacancy ordered structure (Space Group: I 4 /mmm ) with 2ap  × 2ap  × 4ap unit cell, and contains alternate oxygen replete [Co2/Fe2‐O] and oxygen deficient [Co1/Fe1‐O] planes along c‐direction. Room temperature Mössbauer spectroscopy and room temperature neutron powder diffraction confirm the presence of mixed valence states (3+ and 4+) for both Fe and Co. Polaronic behavior in the electrical conductivity is observed below 400 °C, and attributed to the presence of Co 4+ and Fe 3+ cations in the structure. The electrical conductivity at 600 °C is high enough (∼200 S cm −1 ) to act as a cathode material. At the same time, the polarization resistance measurements show an excellent value of 0.1 Ω cm 2 at 600 °C. These results suggest that at 600 °C, this material is a mixed oxide‐ion and electronic conductor exhibiting excellent activity for the oxygen reduction reaction, making it a promising cathode material for an intermediate temperature solid oxide fuel cell.